Actin and microtubule crosslinkers tune mobility and control co-localization in a composite cytoskeletal network. Issue 31 (24th March 2020) - Farhadi, Leila; Ricketts, Shea N.; Rust, Michael J.; Das, Moumita; Robertson-Anderson, Rae M.; Ross, Jennifer L.
Abstract : Microtubules (left) and actin filaments (right) show low mobility when in bundles because actin is swept up into static microtubule bundles. Abstract : Actin and microtubule filaments, with their auxiliary proteins, enable the cytoskeleton to carry out vital processes in the cell by tuning the organizational and mechanical properties of the network. Despite their critical importance and interactions in cells, we are only beginning to uncover information about the composite network. The challenge is due to the high complexity of combining actin, microtubules, and their hundreds of known associated proteins. Here, we use fluorescence microscopy, fluctuation, and cross-correlation analysis to examine the role of actin and microtubules in the presence of an antiparallel microtubule crosslinker, MAP65, and a generic, strong actin crosslinker, biotin–NeutrAvidin. For a fixed ratio of actin and microtubule filaments, we vary the amount of each crosslinker and measure the organization and fluctuations of the filaments. We find that the microtubule crosslinker plays the principle role in the organization of the system, while, actin crosslinking dictates the mobility of the filaments. We have previously demonstrated that the fluctuations of filaments are related to the mechanics, implying that actin crosslinking controls the mechanical properties of the network, independent of the microtubule-driven re-organization.